Studi Implementasi Program Kota Tanpa Kumuh (KOTAKU) di Desa Sokaraja Kidul - Dwi Rahayu Rubianti; Wahyuningrat Wahyuningrat; Simin Simin (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2020)
Kota Tanpa Kumuh (KOTAKU) program is national program to increase infrastructure acces and basic service in urban slum area. Desa Sokaraja Kidul is one of the areas implementing KOTAKU program. The purpose of this research is to find out how the implementation of KOTAKU program at Desa Sokaraja Kidul using What’s Happening perspective by Ripley and Franklin. This research is using qualitative descriptive method. The results of this study indicate that the Implementation of Program KOTAKU (KOTAKU) in Desa Sokaraja Kidul based on dimensions in the perspective of What’s Happening by Ripley and Franklin hasn’t optimal. The following results of the research based on the perspective dimensions of What’s Happening: 1) The Profusion of actors, found that the role of actors at the community level such as BKM and KSM has not been optimal. 2) The Multiplicity and vagueness of goals, The purpose of the KOTAKU Program are understandable and implementing actors understand the program's purposes. 3) The Poliferatin and complexity of government programs, coordination and communication have been effective, policy changes that occur but didn’t have significant impact on the program implementation, Guidelines for program implementation have been made but actors at the community level are not aware of the guidance, the sustainability step in the implementation procedure has not optimally implemented. 4) Community Participation, the people of Desa Sokaraja Kidul support and participate in the implementation of the program. 5) Influencing factors, the funds allocated have not been able to solve all slum problems and social and cultural conditions are factors driving implementation while economic conditions are becoming obstacles to implementation.